Prevalence of Fear of Falling and Its Association with Frailty Among Community-Dwelling Older Adults in Northern Thailand - Juwa , Somkid; Sadjapong, Uratcha; Silangirn, Pongsaton; Juwa, Busarin; Vongruang, Patipat; Thongtip, Sakesun (Unnes Journal of Public Health, 2025)
Frailty in the elderly population is a known risk factor for common geriatric syndromes, contributing significantly to adverse health outcomes. Therefore, we examined the relationship between prevalence of fear of falling and frailty among older adults. A cross-sectional design was employed, and data were collected through in-person interviews conducted between April and May 2024. Participants were selected through simple random sampling from a total of 409 individuals aged 60 years or older, who were included in the analysis.  The fear of falling (FOF) was evaluated using the Short Falls Efficacy Scale International (Short FES-I). Frailty was evaluated using the Thai version of the Simple Frailty Questionnaire (T-FRAIL). The mean age was 69.5 years, and 58.7% were female. The prevalence rates were 47.4% for non-frailty, 39.1% for pre-frailty, and 13.4% for frailty among older adults. Multinomial logistic regression analysis revealed that pre-frail adults had significantly higher odds of high FOF (OR: 5.27; 95% CI: 3.16-8.80, p-value < 0.001), whereas frail adults had significantly higher odds of moderate FOF (OR: 4.37; 95% CI: 1.55-12.32, p-value = 0.005) and high FOF (OR: 17.36; 95% CI: 6.79-44.39, p-value < 0.001) compared to a reference group of non-frail participants. Preventing frailty and pre-frailty among older adults could involve interventions that target various risk factors, such as demographic characteristics, and FOF.